The Unsung Heroes of Welfare Collaboration: Complexities around individuals' contribution to effective inter-agency working in LSCBs. Issue 10 (25th November 2016) - Dudau, Adina; Fischbacher-Smith, Denis; McAllister, Laura
Abstract: The article addresses an under-explored aspect of public partnerships: individuals' role in the effectiveness of collaborations such as the Local Safeguarding Children's Boards (LSCBs) in England and Wales. Building upon theoretical concepts around complex emergence, we conceptualize individuals as conveyors of complex negotiated individual, professional and organizational frames. Shifting focus away from inter-organizational and towards inter-personal communication in partnerships is consistent with miscommunication being the widest recognized problem in collaborations. Qualitative data from policy documents, interviews, and participant and non-participant observation are used to show individuals in the LSCB case study advancing or hindering collaborative work as 'boundary spanners' or 'reluctant' partners.